Spectrophotometric Determination of Catecholamines with Hemoglobin as Catalyst - Hong Chen, Ya; Xia Li, Yan; Shou Tian, Feng (Asian Journal of Chemistry, 2012)
A high sensitive and simple spectrophotometric method for the determination of catecholamines based on their inhibitory effect on the hemoglobin-catalyzed reaction of H2O2 and acid chrome blue K(ACBK) was developed. The concentrations of the catecholamines are in linear relationship with the percentage inhibition (I %) of system under the optimal experimental conditions. The detection limit of the method were 6.1 × 10-8 mol L-1 dopamine, 5.2 × 10-8 mol L-1 adrenaline and 2.4 × 10-9 mol L-1 dobutamine, respectively. This method can be used for the determination of the catecholamines in pharmaceuticals with satisfactory results.